Orientasi Kewirausahaan, Kapabilitas Inovasi dan Keberlanjutan Usaha Keluarga pada Industri Kreatif Sub Sektor Kriya - Tiba, Yakoba Trisan; Situmorang, Tumpal Pangihutan (Jurnal Ilmiah Global Education, 2024)
The aim of this research is to find out what influence’s entrepreneurial orientation, innovation capability, and speed of market entry on the sustainability of family businesses. This research used a quantitative approach, non-probability sampling with a population of ikat business owners in East Sumba District, with 100 respondents from ikat weaving business owners in Kambera District. Data analysis used Structural Equation Modeling Partial Least Square (SEM-PLS). The research results show that entrepreneurial orientation. Strong entrepreneurial orientation can help family businesses to develop and achieve long-term success, innovation capability, the ability of family businesses to generate new ideas and convert them into products, and high speed of market entry can help family businesses to gain competitive advantage. and achieving a larger market share towards the sustainability of the family business is the ability of the family business to survive and develop from generation to generation which has a significant influence on the ikat weaving business.